PENGARUH KEPERCAYAAN KONSUMEN DAN PENGALAMAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA MOTOR SKUTIK 150cc PT INDAH SAKTI MOTORINDO MEDAN - Vikra Seifahlepi; Amirudin, Mella Yunita (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the impact of customer trust on customer loyalty in 150cc scooter motorcycles at PT Indah Sakti Motorindo, to study the impact of customer experience on loyalty, and to assess the simultaneous impact of customer trust & customer experience on customer loyalty in 150cc scooter motorcycles. This research was conducted on PT Indah Sakti Motorindo Medan using a homogeneous population of 48 individuals per month. This study is a quantitative narrative study that uses general news as a research instrument. The data analysis techniques used include validity & reliability test, classical approximation test, multiple linear regression, t test (partial), F test (simultaneous), & determination coefficient. The results based on the multiple linear regression equation show an R-square value of 0.661 or 66.10%, which means that the independent variable contributes significantly to mentioning customer loyalty as much as 66.10%, the remaining interim ad as much as 33.90% is determined by other factors outside the research example. The conclusion based on this study is that customer religion has a significant effect on customer loyalty, customer experience has a significant effect on loyalty, and both simultaneously have a significant impact on customer loyalty at PT Indah Sakti Motorindo Medan for 150cc scooter motorcycles.